2001
DOI: 10.1191/0748233701th100oa
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and cerebrohemodynamics associated with the Persian Gulf Syndrome

Abstract: The Persian Gulf Syndrome generally manifests as a set of nonspecific complaints with emphasis on central nervous system impairment. The purpose of this study was to determine if cognitive performance and middle cerebral artery blood flow velocity (MCABFV) were altered in symptomatic Gulf War veterans (sGWVs) and asymptomatic Gulf War veterans (aGWVs) by exposure to low levels of acetone. MCABFV was assessed in male aGWVs (n = 8) and sGWVs (n = 8) during cognitive challenges while breathing 1) clean air, 2) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Cognitive deficits are among the most common complaints in veterans with GWI with affected veterans performing poorly on neuropsychological tests in tasks relating to executive functioning and memory compared to controls (Sullivan et al, 2003;Anger et al, 1999;Sillanpaa et al, 1997;Binder et al, 1999;Bunegin et al, 2001;Lange et al, 2001;Storzbach et al, 2000). Using a GWI mouse model, we demonstrate that cognitive deficits are present at 16-months post-exposure in mice exposed to GW agents at an early age.…”
Section: Discussionmentioning
confidence: 64%
“…Cognitive deficits are among the most common complaints in veterans with GWI with affected veterans performing poorly on neuropsychological tests in tasks relating to executive functioning and memory compared to controls (Sullivan et al, 2003;Anger et al, 1999;Sillanpaa et al, 1997;Binder et al, 1999;Bunegin et al, 2001;Lange et al, 2001;Storzbach et al, 2000). Using a GWI mouse model, we demonstrate that cognitive deficits are present at 16-months post-exposure in mice exposed to GW agents at an early age.…”
Section: Discussionmentioning
confidence: 64%
“…The lack of effective inhibition as demonstrated in both behavioral performance and in electrophysiological responses may be able to account for multiple other symptomatic complaints. For example, a lack of effective inhibition can represent a plausible etiology for the deficits in executive function [3,8,14,15,58,59], attention [8,[59][60][61][62], and abstraction/problem solving [60,63]. Because it can account for such a wide array of symptoms, impairment in inhibition is compatible with the variety of complaints reported by GW veterans, although they may not specifically report 'a lack of inhibition.'…”
Section: Discussionmentioning
confidence: 79%
“…Several investigations published prior to 2009 concluded that visuospatial and motor skills were poorer and greater dysphoria was evident in deployed veterans with GWI compared to healthy GW veterans ( Anger et al, 1999 ; Axelrod & Milner, 1997 ; Binder et al, 1999 ; Bunegin, Mitzel, Miller, Gelineau, & Tolstykh, 2001 ; Lange, Van Niekerk, & Meyer, 2001 ; Storzbach et al, 2000 ; Storzbach, Rohlman, Anger, Binder, & Campbell, 2001 ; Sullivan et al, 2003 ). A subgroup of GW veterans who were markedly slower on psychomotor tasks was identified in one study, suggesting that there may be subgroups within the GWI population who are markedly impaired ( Anger et al, 1999 ; Storzbach et al, 2001 ).…”
Section: Neuropathology Of Gwimentioning
confidence: 99%